Sustained release of tumor cell lysate and CpG from an injectable, cytotoxic hydrogel for melanoma immunotherapy. Issue 7 (14th March 2023) - Yang, Kui; Zhou, Yuhan; Huang, Biwang; Zhao, Guifang; Geng, Yuan; Wan, Chao; Jiang, Fagang; Jin, Honglin; Ye, Chengzhi; Chen, Jing
Abstract : The fabrication of MCL and the mechanism of MCL-mediated antitumor effects against melanoma. Abstract : Many basic research studies have shown the potential of autologous cancer vaccines in the treatment of melanoma. However, some clinical trials showed that simplex whole tumor cell vaccines can only elicit weak CD8 + T cell-mediated antitumor responses which were not enough for effective tumor elimination. So efficient cancer vaccine delivery strategies with improved immunogenicity are needed. Herein, we described a novel hybrid vaccine "MCL" (Melittin–RADA32 –CpG–Lysate) which was composed of melittin, RADA32, CpG and tumor lysate. In this hybrid vaccine, antitumor peptide melittin and self-assembling fusion peptide RADA32 were assembled to form the hydrogel framework melittin–RADA32 (MR). Then, whole tumor cell lysate and immune adjuvant CpG-ODN were loaded into MR to develop an injectable and cytotoxic hydrogel MCL. MCL showed excellent ability for sustained drug release, to activate dendritic cells and directly kill melanoma cells in vitro . In vivo, MCL not only exerted direct antitumor activity, but also had robust immune initiation effects including the activation of dendritic cells in draining lymph nodes and the infiltration of cytotoxic T lymphocytes (CTLs) in tumor microenvironment. In addition, MCL can efficiently inhibit melanoma growth in B16–F10 tumor bearing mice, which suggested that MCL is a potential cancer vaccine strategy for melanoma treatment.